Prognosis Innovative Approaches in Relation to Results and Complications of Coronary Remedial Surgical Procedure in Case of Acute Coronary Syndrome - A.S. Babadjanov1, S.A. Babadjanov2, M.M. Zufarov3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In modern cardio surgery, it has become possible to predict not only the outcome of surgical interferencein order to save life, but also its effectiveness in terms of the quality of life improvement. It is proved thatcoronaro correcting technologies can not only soften the clinical picture of chronic coronary insufficiency,but also increase the contractility of the ischemic myocardium, as well as significantly improve the patient’squality of life, if the myocardial ischemia has the character of hibernation, and not stanning. The ability todetermine which variant of the ischemic syndrome occurs in the patient before surgery helps to predict theinterference effectiveness. The method used for this purpose (radioisotope scintigraphy, positron emissiontomography, MRI, pharmacological stress echotests) are technically or economically inaccessible, difficultto apply in the perioperative period, and sometimes dangerous.The purpose of the research: to offer an informative, accessible and safe method of preoperative identificationof the hibernating myocardium among patients with IHD for successful prediction of the interferenceeffectiveness.Materials and Method: 83 patients with acute and chronic forms of IHD were under study. In the first group(49 people), there was a coronary stenting (CS). In the second group (34 patients), there was a heart bypasssurgery (HB). There was the comparative assessment analysis in regard to variant of ischemic syndromeand the effectiveness of both operations by means of precardial ECG mapping and stress echotest withdipyridamole.Results: In case of IHD acute forms (acute coronary syndrome, acute myocardial infarction) CS and HBoperations had significant positive dynamics in regard to indicators of coronary blood flow within thecourse of ischemia and myocardial contractility in accordance with precordial mapping (area reductionof ischemia - AST and the decrease of the ischemia degree - ?ST) and stress echotest with dipyridamole(increased contractility of EF indicator and a reduction of ESV, increase in the number of eukinetic segmentsof the myocardium and decrease of hypokinetic segments). We observed the same dynamics, but much lesspronounced, in accordance with ECG mapping and stress echotest data after both operations within thegroup with chronic forms of ischemia.Conclusion: The precardial ECG mapping is informative and available for use in regional cardiosurgicalclinics as a method of the hibernating myocardium identification, which is a more perspective variant ofischemia in case of IHD in terms of left ventricular contractility increase.